Priority-enabled optical shared protection - Fawaz, W. (2007)
The availability of an optical connection is considered to be a critical service differentiator in WDM optical networks. In this regard, the design of a protection scheme that is able to improve the availability of high priority connections while making efficient use of optical resources is a major concern for optical network operators. In a previous work, we proposed the so-called priority-aware shared protection as a potential survivability scheme for next generation WDM networks to deal with the previously exhibited concern. This paper develops an online study whose main purpose is to assess the efficiency of the aforementioned protection scheme. Through this study, we show that the priority-aware shared protection strategy is able to achieve both the best efficiency in terms of resource usage and in terms of availability satisfaction rate compared to existing protection solutions.